2015
DOI: 10.1002/hbm.22748
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic resting state voice network in Parkinson's disease

Abstract: Over 90 percent of patients with Parkinson’s disease experience speech-motor impairment, namely, hypokinetic dysarthria characterized by reduced pitch and loudness. Resting-state functional connectivity analysis of blood oxygen level-dependent functional magnetic resonance imaging is a useful measure of intrinsic neural functioning. We utilized resting-state functional connectivity modeling to analyze the intrinsic connectivity in patients with Parkinson’s disease within a vocalization network defined by a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 54 publications
2
38
1
1
Order By: Relevance
“…According to their studies, the primary vocal circuit consists of the larynx motor cortex and the associated premotor cortex, cerebellum and supplementary motor cortex; the secondary vocal areas include the RO, putamen, ventral thalamus, cingulate motor area and frontal operculum/anterior insula . Previous fMRI studies have found functional anomalies in some of these vocal circuits in PD patients , and our meta‐analysis found structural alterations in these areas. These findings suggest that the morphological changes in these brain regions may give rise to altered function in the vocal network which finally leads to vocal disorders in PD.…”
Section: Discussionmentioning
confidence: 52%
“…According to their studies, the primary vocal circuit consists of the larynx motor cortex and the associated premotor cortex, cerebellum and supplementary motor cortex; the secondary vocal areas include the RO, putamen, ventral thalamus, cingulate motor area and frontal operculum/anterior insula . Previous fMRI studies have found functional anomalies in some of these vocal circuits in PD patients , and our meta‐analysis found structural alterations in these areas. These findings suggest that the morphological changes in these brain regions may give rise to altered function in the vocal network which finally leads to vocal disorders in PD.…”
Section: Discussionmentioning
confidence: 52%
“…Rather than assessing altered activations in different functional systems by conducting task‐based functional magnetic resonance imaging (fMRI) studies, we examined altered functional connectivity within various functional networks robustly defined by meta‐analyses of task‐based neuroimaging studies in a comparative fashion [cf. New et al, ; Schilbach et al, ]. This has the practicable advantage of using easily accessible, short and standardized resting‐state (RS) data while at the same time incorporating the consolidated knowledge based on task‐based imaging into the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Future work could address the hypothesis that speech impairments in PD arise primarily from changes in left cortico‐basal ganglia pathways and that treatment facilitates a functional shift of cortical activity to the right hemisphere. While intriguing, support for this hypothesis is tempered by the fact that speech impairment in PD has also been linked to reduced functional connectivity of right striatal seeds when comparing PD subjects to healthy controls (Elfmarkova et al., 2016; New et al., 2015). However, as previously mentioned, these right‐lateralized findings involved comparing a single heterogeneous group of PD subjects (including those with and without speech impairment) to OHCs.…”
Section: Discussionmentioning
confidence: 99%
“…New et al. (2015) found that PD subjects had reduced connectivity between right and left putamen after performing a seed to seed resting‐state connectivity analysis on thirteen regions involved in vocal motor control (Brown et al., 2005). The study further found that UPDRS Part III speech impairment scores were inversely correlated with right putamen connectivity to right cerebellum and left STG.…”
Section: Introductionmentioning
confidence: 99%